MOUTH BREATHING SYNDROM-AN INTERDISCIPLINARY APPROACH - Iasmina-Alexandra Predescu; Andreea Mihaela Kiș; Dana Emanuela Pitic; Alina Anton; Ștefania Dinu; Mariana Păcurar; Eugen Bud; Ramona Amina Popovici; Mălina Popa; Iustin Olariu (Romanian Journal of Oral Rehabilitation, 2024)
Aim of the study Mouth breathing syndrome (MBS) is a multifactorial condition where the patient breathes predominantly through the mouth instead of the nose, leading to negative consequences on facial development, oral and general health. Because of its complexity, MBS therapy requires close collaboration between different specialities. MBS is not just a respiratory problem; it also affects cranio-facial development, oral health, sleep and even some systemic functions of the body. An interdisciplinary approach ensures a complete evaluation and holistic treatment of the patient, addressing not only the symptoms but also the underlying causes of MBS. Collaboration between specialists allows an individualized treatment, adapted to the specific needs of each patient preventing long-term complications. Involvement of both patient and family in the oral rehabilitation process, supported by the interdisciplinary medical team, is crucial for the success and maintenance of long-term results. Materials and methods The research undertaken aimed to identify the opportunities, challenges and barriers existing in the interdisciplinary approach to complete MBS rehabilitation. The study took into account the responses of 720 specialists from various fields of medicine involved in MBS therapy. Results Dentistry has only 14.5% of recommendation because it is the most represented among the specializations present in the study. Most often, the dentist recommends an ENT specialty or orthodontics. At the top of most frequent symptomatology was sleep disorders, with only 14 doctors specialised in somnology as classified itself as the newest type of the specialty. The most frequent symptomatology (484 responses) is speep apnea followed by 432 answers of orthodontic issues and with close values of dry mouth and halitosis. Conclusions Through collaboration between otolaryngologists, orthodontists, dentists, speech therapists, allergists and other specialists, optimal results can be achieved, improving the general health, craniofacial development and quality of life of patients.